2016
DOI: 10.5624/isd.2016.46.3.159
|View full text |Cite|
|
Sign up to set email alerts
|

Panoramic radiographs underestimate extensions of the anterior loop and mandibular incisive canal

Abstract: PurposeThe purpose of this study was to detect the anterior loop of the mental nerve and the mandibular incisive canal in panoramic radiographs (PAN) and cone-beam computed tomography (CBCT) images, as well as to determine the anterior/mesial extension of these structures in panoramic and cross-sectional reconstructions using PAN and CBCT images.Materials and MethodsImages (both PAN and CBCT) from 90 patients were evaluated by 2 independent observers. Detection of the anterior loop and the incisive canal were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
4
13
0
Order By: Relevance
“…Cone-beam computed tomography (CBCT), is probably the most advantageous method for assessing the anatomy of the AL of the mandibular canal because it gives three-dimensional assessment with no magnification, unsharpness, and distortion, as seen in panoramic radiography (PR) which is otherwise the only alternative to visualize the loop. [678] Thus, the aim of the present study was to assess the presence and course of the AL in the mental foramen region along with identification and analysis of the variations in terms of length, diameter, and height of the AL in males and females in the Eastern Indian population.…”
Section: Introductionmentioning
confidence: 99%
“…Cone-beam computed tomography (CBCT), is probably the most advantageous method for assessing the anatomy of the AL of the mandibular canal because it gives three-dimensional assessment with no magnification, unsharpness, and distortion, as seen in panoramic radiography (PR) which is otherwise the only alternative to visualize the loop. [678] Thus, the aim of the present study was to assess the presence and course of the AL in the mental foramen region along with identification and analysis of the variations in terms of length, diameter, and height of the AL in males and females in the Eastern Indian population.…”
Section: Introductionmentioning
confidence: 99%
“…Many anatomical structures, such as the incisive nerve [ 35 , 39 , 40 ], the alveolar inferior nerve [ 41 ], and its anterior loop [ 40 , 42 ], are more easily visualized on CBCT images [ 14 ] in contrast to 2-D images. Since measurement inaccuracies in CBCT scans can exceed 1 mm, a safety margin of 2 mm from vital structures should be utilized in implant planning [ 21 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“… 8 9 Currently, the most accurate available modality for dentists to quantitatively determine the presence of AL is high-resolution CBCT. 10 According to the literature, major variations have been reported in the prevalence and length of the AL; its prevalence is reported to range from 7.7% 11 to 95.2% 12 and its length from 0.25 mm 13 to 19 mm. 11 It has been suggested that sex, ethnicity, and age differences may exist; 8 9 14 therefore, evaluating the prevalence and length of AL and determining a precise and safe distance from it in different population subgroups can be of clinical significance.…”
Section: Introductionmentioning
confidence: 99%